Self Efficacy and Career Choice Consideration among Undergraduate Students in A Private University in Malaysia - Amira Baharudin, Siti Nor; Yeong Chin, Teo (International Journal of Academic Research in Progressive Education and Development, 2023)
Career choice that determines the role of individuals in the society, is the most critical decision for students who will graduate with diploma and bachelor’s degree. Three aspects of self-efficacy; past performance, vicarious learning, and physiological and emotional reaction, were examined to affirm the positive relationship between undergraduate students’ self-efficacy and career choice. In this study, the relationship of self-efficacy and undergraduate students’ career choice consideration in a private institution in Malaysia was investigated. This research implemented mixed methods to study the aspects of self-efficacy towards the career decision making of 200 undergraduate students from a private university in Malaysia and 10 students were selected for an interview session to find the factors influencing career choice. It was found that physiological and emotional reaction is the strongest contributor to students’ decision in choosing career, followed by students’ sympathetic experience or vicarious learning and the least is the previous or past performance that students achieved. The results indicated that the relationship of self-efficacy and students’ career choice is positive and that universities play a huge role in providing guidance and support for the undergraduates in choosing a career pathway.